Social semiotics of Mẻn Brayut text: systemic functional linguistics perspective - Ketut Suardana (English, 2021)
Mẻn Brayut text is one of Balinese texts develops in Balinese communities. The text is represented in spoken and written text held by Balinese communities. Even more, the text is supported with the statue of Mẻn Brayut found in number of temples in Bali. However, the message conveyed through the text has not been understood yet by most Balinese people. This phenomenon makes the text be interpreted differently. This is because the text has social semiotic conveyed through nonverbal language. Therefore, this research focused on social context embedded in the text of Mẻn Brayut to solve the differences interpretation. The theory used to explore used to analyze the problems is Systemic Functional Linguistics proposed by Halliday. The data were taken from written text (Suwija, 2019). The research used qualitative method since the theory is used as guidance of data collection. The data were collected based on field, tenor, and mode. The result of the result showed that the text described seriousness and sincerity of mother develops the children without having profit orientation, but she emphasizes in profound love. More abstractly, text of Mẻn Brayut represented in statue accompanied by many children placed in number of temples in Bali is interpreted as the propound God’s love for all human.